TRANSMISSION OF CYTOMEGALOVIRUS VIA BREAST MILK IN LOW BIRTH WEIGHT AND PREMATURE INFANTS: A SYSTEMATIC REVIEW - Budiman, Arief (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
The human cytomegalovirus, also known as HCMV, is a herpesvirus that infects around sixty percent of people living in industrialized nations and more than ninety percent of adults living in developing nations. Because infections are typically kept under control by a robust immune response, patients typically have either no symptoms at all or only mild symptoms. Breast milk is regarded as the best diet for newborns because of the anti-infectious properties it possesses in addition to its high nutritional value; yet, breast milk can also act as a vehicle for the transmission of infectious diseases such as viruses and bacteria. Breast milk is the vehicle via which the great majority of human cytomegalovirus (HCMV)-seropositive women pass the virus on to their children. Because their mothers have antibodies that are specific to HCMV, full-term neonates who acquire infections during pregnancy normally show no symptoms and do not experience any difficulties. In contrast, preterm neonates with very low birth weight (VLBW) are more likely to develop symptomatic infections, such as neutropenia, thrombocytopenia, sepsis-like syndrome, and, less frequently, pneumonia and enteric infection. These infections are more likely to occur in VLBW premature newborns. It would suggest that infections that are acquired postnatally clear up on their own without influencing the clinical result. We observe that there is still a risk of ASI-acquired CMV infection in premature newborns whose mothers have a positive CMV antibody test, although the rate of CMV infection is higher in premature infants who are fed fresh breast milk.